Critical reflections on data in second language acquisition - Gudmestad, Aarnes; Edmonds, Amanda, 1979- (Language learning and language teaching, 2018)
"This edited volume offers critical reflections on an essential component of research method in the field of second language acquisition - data. Scholars working on diverse areas (e.g., pragmatics, corrective feedback, phonology) and approaches (e.g., corpus linguistics, concept-oriented analyses, variationism) have come together to identify challenges researchers face when collecting, coding, and analyzing data and to provide guidance for making advancements regarding these aspects of research method. This volume also showcases three types of critical reflection. One involves building a relevant corpus of published investigation and using that database to identify methodological issues in existing research. Another consists of recoding and reanalyzing published work, before reflecting on the impact that these decisions have on observations made about interlanguage. The third begins with a particular area of or approach to second language acquisition and then offers a critical examination on the challenges that characterize the selected area or approach"--